The Secret Service : Kingsman - Millar, Mark; Gibbons, Dave, 1949-; Vaughn, Matthew, 1971-; Lanning, Andy; McKie, Angus; Yu, Leinil Francis; Gho, Sunny (2014)
Around the globe, pop-culture celebrities are being abducted, and no one knows why. Jack London -- superspy -- is on the case. But Jack has problems of his own: a deadbeat sister and her out-of-control son. Young Eggsy has fallen in with the wrong crowd, and his life is circling the drain. Only Jack stands between his nephew and a jail cell. But seeing something of himself in Eggsy, Jack offers him one last chance for a future -- in spy school. Out of his element, surrounded by the best and the brightest, are Eggsy's street smarts enough for him to make it as a secret agent? Does he have what it takes to help his uncle find the celebrities and save the world?
"Contains material originally published in magazine form as The Secret Service #1-6".
"The Secret Service created by Mark Millar, Dave Gibbons and Matthew Vaughn".
Keywords: Secret service -- England -- Comic books, strips, etc; Spies -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Kidnapping -- Comic books, strips, etc; Graphic novels